KONTINUITETA MOTIVA ZMAJA V MAKEDONSKI KNJIŽEVNOSTI 21. STOLETJA NA PRIMERU ROMANA VLADA UROŠEVIĆA ZMAJEVA NEVESTA (Philological Studies, 2019)
This article explores the influence of Slavic folk beliefs in dragons on Macedonian literature, from Marko Cepenkov and the Miladinov Brothers to The Dragon's Bride, a contemporary novel by Vlada Urošević. We examine the parallels between the old and new, tradition and innovation, attitude and interdependence.
Keywords: Macedonian prose, Macedonian folk literature, dragon, mythology